1995
DOI: 10.1128/aac.39.7.1414
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of various gyrA mutants in 451 Staphylococcus aureus strains isolated in Japan and their susceptibilities to 10 fluoroquinolones

Abstract: Point mutations in the gyrA genes of 451 clinical strains of Staphylococcus aureus isolated in Japan were detected by a combination of nonradioisotopic single-strand conformation polymorphism analysis and restriction fragment length polymorphism analysis and by direct sequencing. Six types of gyrA mutations were observed in 149 of the 451 strains (33%), and ofloxacin MICs were greater than 6.25 g/ml for 147 of the 149 strains (98.7%). These mutations were localized between codons 84 and 88, and they were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
(29 reference statements)
5
47
0
1
Order By: Relevance
“…Based on the results of our characterization of 65 Y. pestis Cp r mutants, the most common site of mutation in GyrA is Gly-81. Other studies have indicated that Ser-83 is the most common hotspot for changes in gyrA that result in Cp r (7,11,20,21,23,30). The fact that Gly-81 appears to be a hotspot for mutation in Y. pestis may reflect a difference in the organism's DNA repair capabilities or a difference in the tertiary structure of GyrA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of our characterization of 65 Y. pestis Cp r mutants, the most common site of mutation in GyrA is Gly-81. Other studies have indicated that Ser-83 is the most common hotspot for changes in gyrA that result in Cp r (7,11,20,21,23,30). The fact that Gly-81 appears to be a hotspot for mutation in Y. pestis may reflect a difference in the organism's DNA repair capabilities or a difference in the tertiary structure of GyrA.…”
Section: Discussionmentioning
confidence: 99%
“…The substitutions in Y. pestis GyrA were Gly-81 to Asp or Cys and Ser-83 to Ile or Arg. All of the amino acid substitutions we identified in Y. pestis GyrA have been found in other organisms (4,15,20,23,25,30). Based on the results of our characterization of 65 Y. pestis Cp r mutants, the most common site of mutation in GyrA is Gly-81.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the case for other gram-negative bacteria, DNA gyrase is the primary target for the fluoroquinolones in P. aeruginosa (84). Therefore, the first target-specific mutations are typically observed within the quinolone resistance determining region (QRDR) of gyrA (6,116,165,249,283). The highest levels of resistance are observed in strains that have mutations in the QRDR of both gyrA and the topoisomerase IV gene parC (6,90,91,116,165).…”
Section: Chromosomally Encoded Resistance Mechanismsmentioning
confidence: 99%
“…Meanwhile, several investigators have applied SSCP analysis to the detection of mutations, mainly in gyrA, in several bacterial species (47,203,230,325,331,350). In the most recent study, Takenouchi et al (332) studied gyrA point mutations in 335 clinical P. aeruginosa isolates by nRI-SSCP analysis and direct sequencing.…”
Section: Detection Of Resistancementioning
confidence: 99%